Kontribusi Religiusitas dalam Perilaku Pengambilan Keputusan Konsumsi - Anton Bawono (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2011)
Consequential is one aspect of religiousity, which one is away from any form imposed by Allah s.w.t. Consumption is forbidden by Allah swt is the consumption of haram goods. In this study will look at contributions halalness a product of consumption decisions. This study used four independent variables of quality, halal, price and side effects. The sampling method used was non-probability sampling method using the method of sampling convenience. Analysis of data has using multiple linear regression analysis. The findings of the four variables showed a positive and significant effect, the variable side effects are most dominant variable. While halal variable have the second greatest influence in determining consumption decisions. This suggests that religiosity variable is a variable that determines the capture market share, in the marketing strategy